RELATIONSHIP BETWEEN OBESITY AND HYPERTENSION IN CHILDREN: ANALYSIS BY GENDER AND AGE - Ayik Mirayanti Mandagi; Farapti Farapti; Muji Sulistyowati; Selviani Setyaning Dwiyanti; Zolla Gracia Amardiani; Ahmad Rido'i Yuda Prayogi (Universitas Airlangga, 2026)
Introduction: Obesity is one of the world's most serious health problems. Children are prone to obesity. The current childhood obesity epidemic has been consistently recognized in the scientific literature as a significant predictor of hypertension. Children who are overweight and have hypertension face increased health risks as they grow into adults. In 2019, hypertension in children in Indonesia was 25.9% among senior high children, 29.1% among junior high children, and 40% among elementary children. The obesity rate in children reached 18.8%. Aim: This study aimed to assess gender- and age-related differences in the association between childhood obesity and hypertension. Method: The design of this study was observational and cross-sectional. This study conducted during September until December 2020 in Surabaya City, Rungkut District. This study included 101 respondents aged 9 to 15 years, divided into two age groups: primary school age (9–12 years) and junior high school age (>12–15 years). The Chi-Square statistical test was used to investigate the relationship between childhood obesity and the occurrence of hypertension. Results: Based on the study findings, 11.88% of respondents were obese, and 36.63% had hypertension. Obese children were 3.29 times more likely than normal-weight children to develop hypertension (95% CI: 1.31-8.27, p=0.01). Obesity and hypertension incidence were shown to be significant in female children (OR 4.35, 95% CI: 1.39-13.61, p=0.009) and primary school-aged children (OR 3,5, 95% CI: 1.1-11.13, p=0.03). Conclusion: As a result, knowing the risk factors for hypertension and obesity must be identified in order to prevent them as early as possible.